PSYCHOLOGICAL CHARACTERISTICS OF ADULT PERIOD - Shahklo Sharafullaeva (Scholar Express Journal, 2023)
This article states that adulthood is a period of leadership, caring and maturity, and men and women of this age, like other ages, face psychological changes and crises. The socio-psychological significance of studying psychological problems during adulthood is also emphasized
Keywords: Maturity; gender; psychology; personality